Association between minimum dietary diversity practice in children aged 6-23 months with nutritional status in east Jakarta 2020 - Vahira Waladhiyaputri; Dian Novita Chandra (World Nutrition Journal, 2023)
The effects of malnutrition such as stunting, wasting, and underweight in the 1000 first days of life are irreversible, but is preventable by giving high quality complementary feeding practice. This study aims to examine the relationship between achievement of minimum dietary diversity (MDD) with nutritional status among children aged 6-23 months in East Jakarta during COVID-19 pandemic in 2020.